Analysis of Life Skills of High School Students who Participate in Extracurricular Sports (Study Based on Regional Demographics) - Rajab, Muhammad Oktapian Nur; Gumilar, Agus; Hambali, Burhan (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The purpose of this study was to analyze the level of life skills of high school students in rural areas who take part in extracurricular sports. The method used in this research is a quantitative descriptive method. The participants in this study were high school students in rural areas who participated in extracurricular activities. A total of 240 students were used as participants, consisting of 87 male students and 153 female students. The research instrument used was the Life Skills Assessment Scale (LSAS) developed by Pearson and Kennedy. The results showed that the level of life skills of high school students in rural areas was in a high level category, both those who participated in sports and non-sports extracurricular activities. Meanwhile, the Sig. (2-Tailed) on the Independent Samples Mann-Whitney U test analysis is 0.477. This finding indicates that there is no significant difference in the life skills of high school students who participate in extracurricular sports compared to those who participate in non-sport extracurricular activities (Sig. (2-Tailed) 0.005)